ANALISIS PERSEPSI SISWA LAKI-LAKI DAN PEREMPUAN KELAS X TERHADAP BIDANG STEM SETELAH MENGIKUTI PEMBELAJARAN STEM BERBASIS ENGINEERING DESIGN PROCESS (EDP) DI SEKOLAH MASA DEPAN YOGYAKARTA - Putri Kurniasari; Indah Widiastuti; Valiant Lukad Perdana Sutrisno (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2023)
This study aims to 1) Knowing the perceptions of prospective students of class X schools in STEM through EDP 2) Knowing gender differences in perceptions of prospective students of class X in the field of STEM through EDP. The research design used in this research is experimental research. Data collection refers to the integrated STEM learning module “Mousetrap Car” which is divided into 3 sessions, namely let's build car, mousetrap car, and mousetrap car race. The data and data sources used in this study are qualitative and quantitative data. Qualitative data was obtained from observation and documentation, while quantitative data was obtained from interviews and questionnaires. The sampling technique used is a saturated sampling technique, where all members are sampled. The participants in this study were 28 students of class X sains SMA Masa Depan Yogyakarta. The results of this study can be opened 1) Students' perceptions of EDP-based STEM learning are positive, students show good attitudes and characteristics in learning, students' interests and motivations are positive, but do not really affect students' self-efficacy to choose and study STEM 2). Gender differences in the perceptions of the tenth graders of Future High School in this study did not show a significant difference. Male and female students of class X sains SMA Masa Depan Yogyakarta.